Sosialisasi Penggunaan Media Film Dokumenter dalam Pembelajaran Sejarah di SMA Negeri 6 Palu - Priyatna Prasetyawati; La Samudia Dalili (Lembaga Pengembangan Kinerja Dosen, 2025)
The problems in this community service are: “Can teachers use documentary film media as a learning resource for students at SMA Negeri 6 Palu? The objectives that can be achieved in this service are: (1). Documentary films are well documented and are expected to be a learning resource for students at SMA Negeri 3 Palu, (2) Documentary films can be a source of inspiration for history teachers both in teaching and in making teaching materials, (3) Documentary films can be well selected, which are adapted to subject matter based on the curriculum used. Assistance to the target audience, namely teachers and students to assist in utilizing documentary film learning media as a learning resource for History at SMA Negeri 3 Palu. The hope to be achieved through this community service is that teachers and students can benefit from the use of documentary film learning media in the learning process to improve the quality of both teaching and learning.